Comparative study on the initial oxidation behavior of conventional and nanocrystalline MCrAlY coatings - effect of microstructure evolution and dynamic mechanisms. (15th October 2022) - Zhao, Zongke; Wang, Jinlong; Chen, Minghui; Zhang, Jianqiang; Wang, Fuhui; Young, David J.
Highlights: Two coatings with the same composition but different microstructures are prepared. The nanocrystalline coating was characterized by selective oxidation of Al. The size and shape of β phase is beneficial to the formation of exclusive α-Al2 O3 . Abstract: Two MCrAlY coatings with the same nominal composition but different microstructures are prepared by magnetron sputtering (MS) and arc ion plating (AIP). Their oxidation at 1000°C led to very different results. The relatively coarse grained AIP coating formed a duplex-layer scale, consisting of external θ-Al2 O3 and internal α-Al2 O3, with small amounts of NiCr2 O4 . Severe surface undulation was accompanied by the development of numerous cracks and voids. Aluminum depletion transformed the AIP coating from β to γ, causing volume shrinkage, promoting scale spallation and leading to premature failure. In contrast, the nanocrystalline MS coating was less degraded due to its columnar crystal structure and high-density of grain boundaries which provided rapid Al diffusion. Oxidation of this coating was characterized by a faster θ-Al2 O3 to α-Al2 O3 transformation and formation of an exclusive α-Al2 O3 scale, protecting the surface. Graphical abstract: Image, graphical abstract